Academic competency test-based mathematics learning (ACT-BML): Improving junior high school students’ mathematics achievement - Marzuki; Hamdani; Amalia, Rizki; Sabaruddin (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study examined the association between Academic Competency Test-Based Mathematics Learning (ACT-BML) and improvements in junior high school students’ mathematics achievement. The study was motivated by the implementation of Indonesia’s Academic Competency Test (ACT), which requires instructional approaches that align mathematics learning with standardized academic assessment. In addition, empirical evidence regarding the integration of ACT standards into classroom mathematics instruction remains limited. Method: A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants were 180 ninth-grade students from a junior high school in Langsa City, Indonesia, selected through purposive sampling. The research instrument consisted of 30 ACT-oriented mathematics achievement items that demonstrated satisfactory validity and reliability (Cronbach’s Alpha = 0.872). Data were analyzed using descriptive statistics, a paired-samples t-test, normalized gain (N-Gain), and Cohen’s d effect size. Findings: The results indicated substantial improvement in students’ mathematics achievement following the implementation of ACT-BML. The mean score increased from 37.89 on the pretest to 91.04 on the posttest. The paired-samples t-test revealed a statistically significant difference between the two measurements, t(179) = 54.561, p < .001. Furthermore, the mean N-Gain score was 0.8511, indicating a high level of improvement, while Cohen’s d of 4.07 reflected a very large within-group effect. Significance: This study contributes empirical evidence to the emerging literature on integrating Academic Competency Test standards into mathematics instruction. The findings suggest that ACT-BML may serve as a promising assessment-aligned instructional approach for strengthening students’ mathematics achievement and academic readiness. Nevertheless, further studies employing more rigorous experimental designs are required to establish causal effectivenes.